PENGARUH MODEL PEMBELAJARAN PICTURE AND PICTURE TERHADAP KEMAMPUAN MENULIS KREATIF PUISI BERKENAAN DENGAN KEINDAHAN ALAM PADA SISWA KELAS VII SMP SRIGUNA PALEMBANG - Tania, Ninda Resti (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The problem in this study is is there any influence of the picture and picture learning model on poetry creative writing skills regarding the natural beauty of the Sriguna Palembang VII grade VII students. The purpose of this study was to find out and describe the influence of picture and picture learning models on poetry creative writing skills relating to the natural beauty of the Sriguna Palembang VII grade VII students. The method of this research is the experimental method with the design of the experimental class and the control class. The population of this research was all of the VII grade students of the Sriguna Palembang Middle School, totaling 174 students. The experimental class research sample was 35 students and the control class was 35 students. Data collection techniques used in this study were test techniques, and interview techniques. The data analysis technique used to prove the hypothesis is the t-test. Based on the results of data analysis and discussion, the test level used is a test of 2 (two) parties with a real level α = 0.05 and dk = n - 2, then 70 - 2 = 68. With the value dk (68) then it can it is known for t table = 1.67 (in the attachment to the distribution table value of t) and for the value of t count = 1.72. Thus it can be concluded, that t count> t table (1.72> 1.67) then Ha is accepted because the number of tcount is greater than t table. With the average value of the experimental class 12.88 and the control class 7.88. Thus the hypothesis that the authors say is "There is the influence of the picture and picture learning model has an influence on poetry creative writing skills with regard to natural beauty in Sriguna Junior High School VII grade students" proved the truth.